COMPARISON OF THE EFFECTIVENESS OF PROJECT BASED LEARNING MODEL AND PROBLEM BASED LEARNING IN MATHEMATICS LEARNING AT PUBLIC JUNIOR HIGH SCHOOLS WITH A ACCREDITATION IN MAKASSAR CITY - Putu Ayu Suyastini (Universitas Negeri Makassar, 2017)
The research aims to discover the comparison of the affectiveness of project based learning and problem based learning in Mathematics learning in class VIII at Public Junior High Schools (SMPN) with A Accreditation in Makassar City. The research is Quasi Experiment with pretest-posttest design. The populations of the research were all of the students of class VIII at SMPN with A Accreditation in Makassar City and the samples were class VIII/B4 at SMPN 5 Makassar and class VIII2 at SMPN 26 Makassar which were chosen by using cluster random sampling technique. The data of the research were analyzed by using descriptive and inferential analysis. The results of the research reveal that both descriptively or inferentially, project based learning model have met effectiveness creteria that the average score of students’ Mathematics postt-test who were taught by using project based learning model is in high category by 81.87 and deviation standard 8.75, classical completeness is 87%, the average of normalized gain is in high category, the students’ activities are in very active category, the students’ responses on learning model are positive and students’ learning interests are in very high category. While inferentially, class classical completeness is ineffective. Generally, it is concluded that project based learning model is effective to be implemented in Mathematics learning in Two Variable Linear Equation System material in class VIII/B4 at SMPN 5 Makassar. The scores os students’ Mathematics learning results who were taught by using problem based learning model both descriptively and inferentially based on the post-test results are in high category with the average score 18.10 and deviation standard 7.73, the average of normalized gain is in high category, classical completeness is 86%, the students’ activities are in very active category, the students’ responses on learning model are postive, and the students’ learning iterests are in high category. While inferentially, class classical completeness is ineffective. Generally, it is concluded that problem based learningmodel is effective to be implemented in Mathematics learning in Two Variable Linear Equation System material in class VIII 2 at SMPN 26 Makassar. The results of hypothesis test at the significant level α = 0.05 with t-test indicates that Ho is accepted meaning that there is no difference of effectiveness between project based learning model and problem based learning model in Mathematics learning in Two Variable Linear Equation System material and variables of class VIII students at SMPN with A Accreditation inMakassar City